A atuação do Conselho Municipal de Habitação de interesse social em Belém - PARENTE, Eneida Barbosa (Universidade Federal do Pará, 2014)
This paper aims at analyzing the performance of the City Council for Social Housing ( CMHIS ) while policy management Social Housing in the City of Bethlehem from 2005 until 2012 . The specific objectives are intended to identify and analyze the composition of CMHIS , and analyze the dynamics and structure , noting that the Council can maintain autonomy in decision -making and participation of civil society , as well as observe the process of elaboration of the Municipal of Social Housing 2012, the jurisdiction of the board . . The methodological approach was guided by qualitative research , and used as tools to bibliographic and documentary research , and field research with the application of semi-structured interviews to members of the City Council for Social Housing . The survey results indicated that CMHIS as an instrument of mediation between the government and civil society in policy Social Housing , was not (for the most part of its history ) and is not in line with the objectives set in its creation , it was the guarantee of social participation in the management of social housing policy in Bethlehem Only in the period from 2011 to 2012 , when preparing the Municipal Plan for social Housing , the CMHIS exercised its functions effectively.